Feasibility and safety evaluation of ultra-remote robot-assisted laparoscopic hysterectomy - Juyuan Huang; Li'an Li; Jing Cheng; Jing Liao; Yurou Chen; Yi Peng; Sha Wang; Qiongyan Zou; Guoyan Zhao; Wei Zhao; Mengya You; Jingying Yang; et al. (Intelligent Surgery)
Objective: To assess the safety and feasibility of ultra-remote robot-assisted laparoscopic hysterectomy using the Edge Multi-Port Endoscopic Surgical Robot MP1000 (Shenzhen Edge Medical Co., Ltd., Shenzhen, China) combined with 5G communication technology. Methods: A case of remote robot-assisted laparoscopic hysterectomy was successfully completed on May 2024 by using the Edge Multi-Port Endoscopic Surgical Robot MP1000 at Zhongnan Hospital of Wuhan University and the People's Liberation Army General Hospital, approximately 1, 200 ​km apart. The procedure was simultaneously broadcast during the 36th Annual Meeting of the International Society for Gynecologic Endoscopy in Conjuction with the Peking University Gynecologic Oncology Summit Forum. Results: A 49-year-old female was hospitalized in the Department of Gynecology of Zhongnan Hospital of Wuhan University for frequent urination for half a year and increased menstrual flow for over a month. The patient was diagnosed with abnormal uterine bleeding caused by multiple uterine leiomyoma and endometrial polyps, combined with moderate anemia. There were no contraindications for surgery, and the patient had surgical indications. On May 2024, the patient underwent a 5G remote robot-assisted laparoscopic hysterectomy and bilateral salpingectomy under general anesthesia. The procedure was successful, with no surgical complications and no interruptions during the live broadcast. The intraoperative blood loss was approximately 20 ​mL, and the surgery lasted about 70 ​min. The bidirectional latency during the operation was around 19 ​ms, with no adverse events related to the robot or the network. The patient recovered well postoperatively and was discharged on the fourth day with no postoperative complications. Conclusion: Preliminary findings indicate that ultra-remote robot-assisted laparoscopic hysterectomy is safe and feasible with the support of 5G communication technology. This surgery represents the first globally broadcast remote procedure in the field of gynecology, marking a new milestone in the stability and safety of China's remote medical technology. Remote robotic surgery is expected to be widely promoted in the future, providing services to patients in areas with limited medical resources.